2020
DOI: 10.11591/ijeecs.v20.i1.pp222-230
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric-type dispersion maps in dispersion-managed optical link with mid-span spectral inversion

Abstract: In long-haul optical communication systems consisting of single-mode fiber spans and fiber amplifiers, such as an erbium-doped fiber amplifier, signal distortion causes performance to deteriorate because of group velocity dispersion and fiber nonlinearity. A combination of dispersion management and optical phase conjugation is an effective technique of compensating for the distortion. In an optical link configured with this combination, the dispersion map mainly affects the compensation for the distorted optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…One approach to supplement the incomplete compensation by the difficulty of symmetry in MSSI is the combination of DM link configuration [6,7]. Authors have also confirmed the compensation improvement of 960 Gb/s wavelength division multiplexed (WDM) transmission in MSSI-based DM link [13][14][15]. In our researches related with the applying MSSI into DM link, the various DM configurations have been proposed by using non-uniform RDPSs, such as artificial distribution of arbitrary RDPSs, random distribution of various RDPSs, and asymmetric dispersion map with respect to midway OPC, to expand flexibility of link configuration.…”
Section: Introductionmentioning
confidence: 85%
“…One approach to supplement the incomplete compensation by the difficulty of symmetry in MSSI is the combination of DM link configuration [6,7]. Authors have also confirmed the compensation improvement of 960 Gb/s wavelength division multiplexed (WDM) transmission in MSSI-based DM link [13][14][15]. In our researches related with the applying MSSI into DM link, the various DM configurations have been proposed by using non-uniform RDPSs, such as artificial distribution of arbitrary RDPSs, random distribution of various RDPSs, and asymmetric dispersion map with respect to midway OPC, to expand flexibility of link configuration.…”
Section: Introductionmentioning
confidence: 85%
“…Due to the rapid development, optical fiber communications have become one of the most important factors for modern communication systems [1][2][3][4]. This is why modern communication networks have become more sophisticated.…”
Section: Introductionmentioning
confidence: 99%